Uptake of antepartum care services in a matrilineal-matrilocal society: a study of Garo indigenous women in Bangladesh - Suban Kumar Chowdhury (BMC, 2023)
Abstract Background The indigenous Garo is a close-knit matrilineal-matrilocal community. This community's expectant mothers receive less antepartum biomedical care, making them prone to maternal mortality. This study developed a conceptual framework to explore how the external environment, personal predispositions, enabling components and perceived antepartum care needs influence and generate a gap in antepartum biomedical care uptake. Methods The author used qualitative data from the study area. The data were collected through conducting 24 semi-structured interviews with purposively selected Garo women. After transcribing the data, the author generated the themes, grouped them into two broader domains, and analyzed them using the grounded theory approach. Results The emergent themes suggest adding the external environment (i.e., healthcare facilities' availability and services and culturally relevant healthcare services) to Anderson's behavioral model to understand indigenous women's antepartum care uptake disparity. Antepartum care uptake disparities arise when Andersen's behavioral model's other three drivers-personal predisposition, enabling components, and needs components-interact with the external environment. The interplay between enabling resources and the external environment is the conduit by which their predispositions and perceived needs are shaped and, thus, generate a disparity in antepartum care uptake. The data demonstrate that enabling resources include gendered power dynamics in families, home composition and income, men's spousal role, community practices of maternal health, and mother groups' and husbands' knowledge. Birth order, past treatment, late pregnancy, and healthcare knowledge are predispositions. According to data, social support, home-based care, mental health well-being, cultural norms and rituals, doctors' friendliness, affordable care, and transportation costs are perceived needs. Conclusions Garo family members (mothers/in-laws and male husbands) should be included in health intervention initiatives to address the problem with effective health education, highlighting the advantages of biomedical antepartum care. Health policymakers should ensure the availability of nearby and culturally appropriate pregnancy care services.